2012
DOI: 10.1073/pnas.1211484109
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two functionally redundant RNA elements in the coding sequence of poliovirus using computer-generated design

Abstract: Genomes of RNA viruses contain multiple functional RNA elements required for translation or RNA replication. We use unique approaches to identify functional RNA elements in the coding sequence of poliovirus (PV), a plus strand RNA virus. The general method is to recode large segments of the genome using synonymous codons, such that protein sequences, codon use, and codon pair bias are conserved but the nucleic acid sequence is changed. Such recoding does not affect the growth of PV unless it destroys the seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 33 publications
4
53
0
Order By: Relevance
“…Some of the alanine substitutions in our study (S416A, L419A, and L420A) involved changes in the sequence of an RNA element within the 3D gene (42), but the RNA sequences within the 3D gene are unlikely to affect the frequency of replicative RNA recombination. Two of these alanine substitutions (S416A and L419A) exhibited increased RNA recombination, whereas the third (L420A) exhibited dramatically reduced RNA recombination.…”
Section: Dmentioning
confidence: 70%
See 1 more Smart Citation
“…Some of the alanine substitutions in our study (S416A, L419A, and L420A) involved changes in the sequence of an RNA element within the 3D gene (42), but the RNA sequences within the 3D gene are unlikely to affect the frequency of replicative RNA recombination. Two of these alanine substitutions (S416A and L419A) exhibited increased RNA recombination, whereas the third (L420A) exhibited dramatically reduced RNA recombination.…”
Section: Dmentioning
confidence: 70%
“…Two of these alanine substitutions (S416A and L419A) exhibited increased RNA recombination, whereas the third (L420A) exhibited dramatically reduced RNA recombination. The role of 3D pol in replicative RNA recombination is generally accepted (21,25), while the functions of RNA elements in the 3D gene remain ambiguous (42,43). Consequently, we attribute phenotypic changes in the frequency of RNA recombination to the alanine substitutions in 3D pol rather than to changes in RNA sequences encoding 3D…”
Section: Dmentioning
confidence: 85%
“…This describes the frequency of synonymous codon pairs that does not fit the use of individual codons (16)(17)(18) (1). The loci of three replication-essential hairpin structures, Cre (81), and α and β (23,24), as well as the conserved but not-essential RNase L ci element (25,26), are shown above the PP. The SnaB I and Bgl II restriction sites, used for subcloning the P2 and P3 domains, are indicated.…”
mentioning
confidence: 99%
“…However, the dynamics of their interactions within host cells and the role of other regions of structured RNA remain to be fully characterized. For example, two recent studies revealed a number of novel structures within the ORF (Burrill et al, 2013;Song et al, 2012), one of which -element 3D-7000 -is implicated in RNA replication through an as yet unknown mechanism (Burrill et al, 2013).…”
Section: Picornavirusesmentioning
confidence: 99%